Peran Orang Tua Mendampingi Anak Belajar di Rumah Saat Pandemi Covid-19 - Nuratika, Silvi; Ridha, Usfur (Jurnal Riset dan Pengabdian Masyarakat, 2021)
The current Covid-19 pandemic situation has caused parents to be involved in every child's learning at home, this is because there are rules for learning from home to prevent the spread of Covid-19. This article aims to discuss the role of parents in accompanying or accompanying children to study at home during the Covid-19 pandemic. The method used is the literature review method through books and journals. The results show that the role of parents accompanying children during the Covid-19 pandemic is to motivate children, facilitate children's learning needs, evaluate children's learning outcomes, become teachers who guide and direct children, and create a conducive environment and a comfortable situation.